Panax ginseng – A review - Majid, Alyaa (University of Thi-Qar Journal of Science, 2019)
Ginseng has been traditionally utilized for several millennia in Asian countries, including Korea, China, and Japan, not only as a nourishing and tonifying agent but also as a therapeutic agent for a variety of diseases. In recent years, the different impacts of panax ginseng including immunity improvement, blood circulation improvement, antioxidation and anticancer an effect have been reported in clinical as well as basic research. Around the world, there is a trend of the rising utilization of health functional foods on the level of disease prevention along with increased interest in maintaining health because of population aging and the awareness of lifestyle diseases and chronic diseases. But till now, international ginseng monographs including those of the World Health Organization have been based on data on white ginseng and have mentioned red ginseng only partly. Another botanical species, although commonly called Siberian ginseng (Eleutherococcus senticosus), is not a true ginseng. The present monograph will contribute to providing accurate information on panax ginseng to agencies, businesses, and consumers both in Iraq and abroad.